Effectiveness of Brand Management Key Elements in Forming Consumer Loyalty - Catur Sugiarto; Pram Suryanadi (Universitas Sebelas Maret, 2019)
The competitive strength of companies in the current era of global trade is largely determined by the company's ability to manage their brands. The implementation of an effective brand management strategy was proven to have an impact on the formation of competitive advantage through a form of commitment and customer loyalty to the company's brand. This study aims to examine the role of key elements of brand management in shaping customer loyalty. The quantitative study was conducted in order to investigate the effect of brand innovativeness, brand customer orientation, brand self-relevance, and brand social responsibility on brand commitment. 252 responses from Indonesian respondents were collected and then analyzed with Structural Equation Modeling (SEM). The results prove that the four key elements of brand management have a great influence on the formation of brand commitment and loyalty.